Knowledge, attitudes, and perceptions about antibiotic use and antimicrobial resistance among final year undergraduate medical and pharmacy students at three universities in East Africa - Lubwama, Margaret (PLoS One, 2021)
INTRODUCTION: Proper measures to combat antimicrobial resistance development and spread in Sub Saharan Africa are very crucial bearing in mind the projected burden of antimicrobial resistance which is expected to be increase by 2050. Training of medical doctor and pharmacy students in antimicrobial stewardship is vital to combat antimicrobial resistance. This study was designed to evaluate the knowledge, attitude, and perception of final year medical and pharmacy students on antimicrobial use and antimicrobial resistance at three universities in Uganda, Kenya, and Tanzania. METHODOLOGY: A cross-sectional survey was carried out among final year undergraduate medical and pharmacy students at three universities in East Africa. A Self-administered questionnaire was developed which included dichotomous questions and questions using a 4-point Likert scale. The questions were based on knowledge and attitude about antibiotics, and preparedness to use antibiotics in clinical scenarios. Data were analyzed using STATA version 16 following the objective of the study. RESULTS: Three hundred and twenty-eight final year students participated in the survey from MUK 75, MKU 75 and CUHAS 178. Slightly majority of participants were male 192(58.5%) and their median age was 25 [23 – 27] years. In general, 36.6% (120/328) of students had good overall total knowledge. More students at MUK had good knowledge compared to MKU, and CUHAS (72% vs, 40% vs. 20.2%; p<0.001). The mean scores for overall good total knowledge, general knowledge about antibiotics, knowledge about antibiotic resistance, and knowledge about antibiotic use in clinical scenarios were 58% (CI: 57%– 60%), 95% (CI: 94%– 97%), 54% (CI: 52% - 56%), and 46% (CI:44% - 48%) respectively. More pharmacy students compared to medical students had a good attitude and perception on antibiotic use (79.6% vs. 68.4%; p = 0.026). The students at CUHAS perceived being more prepared to use antibiotic in district hospitals compared to MKU and MUK (75.3% vs. 62.7% vs. 65.3%; p = 0.079). While two hundred and seventy (82.3%) students perceived knowing when to start antimicrobial therapy, 112 (34.2%) did not know how to select the appropriate antibiotic (p<0.0001), 97 (29.6%) did not know the antibiotic dose to give (p<0.0001), and 111 (33.8%) did not know when to switch form an intravenous antibiotic to oral regimen (p<0.0001). CONCLUSION: Final year students have low scores in knowledge about antimicrobial resistance and antibiotic use in clinical scenarios. This has exposed gaps in practical training of students, while they may feel confident, are not fully prepared to prescribe antibiotics in a hospital setting. A multidisciplinary and practical approach involving medical schools across the East African region should be undertaken to train final year undergraduate students in antimicrobial resistance and antimicrobial stewardship programs. Antimicrobial resistance and antimicrobial stewardship courses should be introduced into the curriculum of final year medicine and pharmacy programs.